The Human Resource Competency at the One-Roof Integrated Administration System (SAMSAT) Office of Gowa Region - Zulfa Khaeria Jufri; Djamil Hasim; Asmadianto Asmadianto; Dahlan Dahlan (Universitas Negeri Makassar, 2019)
The limited quantity and quality of human resource at One-Roof Integrated Administration System (SAMSAT) Office of Gowa Region requires an improvement in terms of knowledge, skills and self-concept competency / attitude. Based on the fact of the accumulated taxpayer data and the occurrence of public complaints on the competency of human resource in providing information that is not transparent, service time is quite long, and the condition of public services that have not been conducively provided. This research uses descriptive qualitative research with data collection techniques are through interviews, observation, and documentation. The validity checking of the data is carried out through triangulation, and member check. Data analysis techniques use condensation data, data presentation, and conclusion drawing. Changes and developments in technology are increasingly advanced, fast and can be connected in various organizational systems that require the competency of the human resource to provide excellent service. With this improvement of the human resource competency in producing human resource that have the knowledge, skills, and self-concept / attitude, may become the important key to be able to fullfill the public demands at the One-Roof Integrated Administration System (SAMSAT) Office of Gowa Region.